Criminal Liability of Children in Online Gambling Promotion and the Restorative Approach - BANI, Feny Nursya’; FAHREIN, Shenna Ismi; BHAKTI, Tegar Yuda (Indonesia Strategic Sustainability, 2025)
The phenomenon of increasing involvement of children in online gambling promotion raises a complex legal dilemma, especially regarding the balance between protecting children's rights and providing criminal accountability. Children who are still in the cognitive and emotional development stage are often involved in online gambling promotion without a full understanding of the long-term impacts, both for themselves and society. However, a criminal law approach that prioritizes repressive sanctions without considering rehabilitative aspects risks damaging children's futures and exacerbating social problems. This study examines the effectiveness of the juvenile justice system in Indonesia in handling online gambling promotion cases. It assesses the urgency of implementing a restorative approach as a fairer and more recovery-oriented alternative. The restorative approach emphasizes the restoration of relationships between perpetrators, victims, and the community so as to avoid stigmatization and provide opportunities for children to improve their behavior. The results of this study emphasize that the legal system must prioritize the principle of rehabilitation rather than punishment alone in order to ensure child protection while preventing the recurrence of criminal acts. Thus, the application of restorative justice in cases of children involved in online gambling promotion is a strategic step to create a more humane and future-oriented justice system.